Electric Field-induced Semiconductor-to-Semimetal Transition in Monolayer Bi2C3: A First-Principles Investigation - Chuong, Nguyen Van; Truong, Pham Thiet; Hoa, Le Thi; Bich, Tran Ngoc; Phuc, Huynh Vinh; Hieu, Nguyen Van; Hieu, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics; Vol 42 No 2, 2026)
In this work, we perform comprehensive first-principles calculations to investigate the structural, mechanical, electronic, optical, and field-tunable properties of a newly proposed two-dimensional (2D) material, monolayer Bi 2 C 3 . Structural optimization and phonon spectrum analysis confirm its dynamical stability. The Bi 2 C 3 monolayer adopts a buckled honeycomb-like configuration, characterized by strong C-C sp 2 bonding and Bi-C sp 3 hybridization. Our analysis of its mechanical properties reveals significant anisotropy, with a maximum Young’s modulus of 28.85 N/m. Monolayer Bi 2 C 3 is an indirect semiconductor, with a PBE/HSE06 band gap of 0.82/1.37 eV. Furthermore, the material exhibits strong and broad light absorption, spanning from the visible to the ultraviolet region, with a maximum absorption coefficient of 6.50 × 10 5 cm -1 . Most importantly, we demonstrate that the band gap of Bi 2 C 3 can be effectively tuned by applying a perpendicular electric field. This electric field induces a progressive reduction in the band gap, ultimately driving a semiconductor-to-semimetal transition. These findings demonstrate that monolayer Bi 2 C 3 is a dynamically stable 2D semiconductor with highly tunable electronic and optical properties, positioning it as a promising candidate for next-generation electronic and optoelectronic applications.